Penegakan Hukum Pemilu di Indonesia Dalam Mewujudkan Pemilu Yang Adil, Transparan, dan Berkualitas - Nuribadah; Muksalmina (ENLEKTURER: Journal of Islamic Studies, 2024)
The number of cases of violations that occurred in the process and implementation of elections, both administrative violations, election crimes, violations of the election organizers' code of ethics, Disputes between Election Participants (PSAP), Election Contestant Disputes with Election Organizers (PSPP). This research was created to analyze election law enforcement in Indonesia, with a focus on disputes that occur between election contestants (PSAP), disputes between election contestants and election organizers (PSPP), which are based on constitutional law, associated with theories which is relevant. In this study, the authors used a normative juridical method by analyzing data through a review of literature or secondary data which included primary legal raw materials, secondary legal materials and tertiary legal materials, both in the form of documents and applicable laws and regulations related to normative juridical analysis. implementation. election and election law. The results of the study show that: Election law enforcement and settlement is carried out by Bawaslu, Provincial Bawaslu, and Regency/Municipal Bawaslu with the authority to settle election process disputes and processes according to their respective levels, with the process of receiving requests, reviewing requests through formal verification and material verification, conduct mediation between disputing parties, conduct adjudication between disputing parties and decide. Bawaslu accepts the PSPP request as a result of the issuance of a KPU decision in the form of a Decree and/or Minutes. So that the elections to be held in 2024 can run according to the applicable laws and regulations. It is recommended that in upholding election law, election administration (KPU), Bawaslu and election participants, they must be able to guarantee free and fair elections, by guaranteeing the constitutional rights of all parties in a proportional and fair, honest and fair manner, as well as election results. which legitimizes the presence of leaders in accordance with the people's choice.